If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 = 2x + 4(4x + -13) Reorder the terms: 56 = 2x + 4(-13 + 4x) 56 = 2x + (-13 * 4 + 4x * 4) 56 = 2x + (-52 + 16x) Reorder the terms: 56 = -52 + 2x + 16x Combine like terms: 2x + 16x = 18x 56 = -52 + 18x Solving 56 = -52 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 56 + -18x = -52 + 18x + -18x Combine like terms: 18x + -18x = 0 56 + -18x = -52 + 0 56 + -18x = -52 Add '-56' to each side of the equation. 56 + -56 + -18x = -52 + -56 Combine like terms: 56 + -56 = 0 0 + -18x = -52 + -56 -18x = -52 + -56 Combine like terms: -52 + -56 = -108 -18x = -108 Divide each side by '-18'. x = 6 Simplifying x = 6
| 14/x=2/5 | | 2y*2+12y+10=0 | | -115/6-21/9 | | 0=12m^2n^2-8mn+1 | | 8/x=14/8 | | 15=32-6 | | 3(8-2w)=-2x-6 | | b/-16=-7 | | 9+3x=x+9 | | 2(a-8)+7=5(a+2)-4a-19 | | (20x^2-12x+8)/(2x+8) | | 5/6=x/15 | | 69.08=6.28(x+4) | | 12x^2+29x+14=0 | | 3x^2+10=-26 | | 116=6x+5(6x-10) | | -8x+1=9+x | | X/12=24/36 | | y=-2+6x+x^2 | | 256-9x=-257 | | [3x-1]=4 | | 12x^5-6x^3-18x=0 | | 4(3a+1)+6(3-a)= | | x-15=4n | | 3(-1+6x)=-75 | | 108=7x+3 | | y=0.498x-973.9 | | 56=2x+4 | | (2x-1)*(2x-1)=625 | | 4(y+5)3=35 | | 21/8x-21=0 | | y^2=1.21 |